2022
DOI: 10.1097/tp.0000000000003817
|View full text |Cite
|
Sign up to set email alerts
|

Renal Normothermic Machine Perfusion: The Road Toward Clinical Implementation of a Promising Pretransplant Organ Assessment Tool

Abstract: The increased utilization of high-risk renal grafts for transplantation requires optimization of pretransplant organ assessment strategies. Current decision-making methods to accept an organ for transplantation lack overall predictive power and always contain an element of subjectivity. Normothermic machine perfusion (NMP) creates near-physiological conditions, which might facilitate a more objective assessment of organ quality before transplantation. NMP is rapidly gaining popularity, with various transplant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
50
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(50 citation statements)
references
References 151 publications
(230 reference statements)
0
50
0
Order By: Relevance
“…Hamelink and colleagues have recently published an overview of the current renal NMP protocols used globally, demonstrating the diversity in perfusion protocols. 21 Ellliot and colleagues have published a review on the rationale of NMP protocols and perfusate components necessary for a clinically viable protocol. 22 For NMP to be clinically viable, perfusate must contain at least: a (red blood cell) based oxygen carrier, a crystalloid-/colloid-based solution to maintain volume, mannitol, a vasodilator, corticosteroids to reduce inflammation, support of metabolism through glucose and amino acids, insulin to increase absorption of glucose, and a buffer to maintain pH (usually sodium bicarbonate).…”
Section: Discussionmentioning
confidence: 99%
“…Hamelink and colleagues have recently published an overview of the current renal NMP protocols used globally, demonstrating the diversity in perfusion protocols. 21 Ellliot and colleagues have published a review on the rationale of NMP protocols and perfusate components necessary for a clinically viable protocol. 22 For NMP to be clinically viable, perfusate must contain at least: a (red blood cell) based oxygen carrier, a crystalloid-/colloid-based solution to maintain volume, mannitol, a vasodilator, corticosteroids to reduce inflammation, support of metabolism through glucose and amino acids, insulin to increase absorption of glucose, and a buffer to maintain pH (usually sodium bicarbonate).…”
Section: Discussionmentioning
confidence: 99%
“…During NMP, organs are perfused with a blood-based solution at 37 • C, mimicking the physiological conditions to support metabolic activity and organ function (52). The perfusate composition between NMP protocols varies greatly, as the exact metabolic needs of an isolated kidney are still not fully characterized (70,71). Having said that, studies have revealed the importance of using an oxygen carrier (e.g., red blood cells or artificial oxygen carriers), even when supraphysiological concentrations of oxygen are used (72,73).…”
Section: Normothermic Machine Perfusionmentioning
confidence: 99%
“…Independent of the organ preservation temperature, the optimal start time of machine perfusion (initial (on the procurement site)-continuous-at the end of preservation (at the recipient center)) depends mainly on the aim of its clinical application, in particular, preservation, organ quality assessment or organ repair. Figure 3 summarizes the wide range of machine perfusion strategies as described in recent publications [6,13,87,95]. NMP as an assessment tool has probably a wider range of options as compared with HMP(±O 2 ), at the donor hospital, recipient center or for the whole time of organ preservation [13].…”
Section: Prospects: When To Start (Oxygenated) Machine Perfusion?mentioning
confidence: 99%
“…Figure 3 summarizes the wide range of machine perfusion strategies as described in recent publications [6,13,87,95]. NMP as an assessment tool has probably a wider range of options as compared with HMP(±O 2 ), at the donor hospital, recipient center or for the whole time of organ preservation [13]. Multiple reasons explain the current limited implementation of NMP in clinical practice: technically complex, time-consuming, risk of organ loss in case of technical failure, the high cost of NMP (disposables, perfusate components, analyses for viability assessment), the need of a permanent availability of a dedicated staff (surgeons/perfusionists) and a specialized perfusion room.…”
Section: Prospects: When To Start (Oxygenated) Machine Perfusion?mentioning
confidence: 99%
See 1 more Smart Citation